Religion and political engagement - Aghazadeh, Jafar (Cogent social sciences, 2017)
The present research examined Relationship between Religion and political engagement in Iran. Political engagement is very important for political stability and dynamism of societies. Political engagement has been one of the concerns of thinkers and cultural and intellectual circles of the world in recent years. The necessity of the participation of the youth is something which has been seriously taken into account in different phases of the development process of societies. The importance of Political Behavior is to the extent that in national strategic planning, developing regulated participation of people in decision-making procedures has considered as a strategy. Survey method was employed here for collecting and analyzing data. The research population included the entire citizens of the city of Isfahan in September and October of 2011. The sample included 360 people who were selected by cluster-sampling. For data collection, questionnaire was employed whose validity and reliability were evaluated using formal method and Cronbach’s Alpha. Results showed that there exists a direct relationship between the level of religiousness and Political Behavior. According to these findings, we may expect higher Political Behavior among people in religious societies.